Historical Reenactment - McCalman, Iain. author. aut Link
XI, 229 p. 12 illus.
Keywords: Since the late 1700s new forms of visual entertainment have tried to simulate the details of nature: reenactment has now become the most widely-consumed form of popular history. This book engages with the quest for definition and appropriate delimitation of reenactment as well as questions about the relationship between realism and affect.